Large current account deficits and neglected vulnerabilities - Aromí, José Daniel (2018)
Using a sample covering 46 advanced and emerging economies over 1990-2017, it is found that large current account deficits are reversed significantly faster than what forecasters anticipate. In addition, large current account deficits are followed by negative surprises in economic growth, low asset returns and drops in sentiment. These regularities are observed for advanced and emerging economies. Analyses for different sample periods do not point to a gradual reduction in the reported patterns. These findings are indicative of systematic neglect of vulnerabilities and have implications for the understanding of past economic events and the design of macro-prudential policies.